Modern Epidemic Situation of Parenteral Viral Hepatitis and Drug Addiction in the Russian Federation and Moscow - Yu. B. Novikova; A. A. Asratyan; E. V. Rusakova (Эпидемиология и вакцинопрофилактика)
Study aim - a comparative analysis of dynamics and trends in the prevalence of viral hepatitis B and C and drug addiction in Russia and Moscow in the period from 1999 to 2014. Materials and methods. A retrospective analysis of the prevalence of viral hepatitis B and C, and drug addicts was performed among the population of Moscow and the Russian Federation for the period from 1999 to 2014. The forms of federal statistical observation were applied. To assess the significance of differences between the compared values, the statistical significance error (p) were calculated based on the calculation of Student's test (t). Results and discussion. The tendency of growth in prevalence of drug addiction was verified over the study period in Moscow and in Russia as a whole (in Moscow, 166.3 (1999) to 257.37 100 ths people (2013), in Russia 154.75 (1999) to 227.19 100 ths people (2013)). However, the growth rate of drug addiction prevalence has decreased in recent years mainly due to the decrease in the number of patients who applied for medical help for the first time. It was shown that a composition of the consumed drugs has changed in the studied period in Russia: Portion of cannabinoid addiction has decreased in 2 times, the abuse of stimulants in 19 times. The opium addiction compiled the main portion of consumed drugs (74.5%), the poly addiction - 18.3%, the proportion of addiction to stimulants was 3.5%. Epidemiologic features of the of parenteral viral hepatitis B and C was demonstrated: Reduced prevalence of acute forms and an increased incidence of chronic forms of hepatitis B and C in the population of Moscow; changes toward older age in representation of hepatitis B and C; sexual transition was defined as a main transition way for hepatitis B and C. For the first time it shows a very strong positive correlation (r = from 0.95 to 0.96) between the primary drug addiction and the incidence of acute forms of hepatitis B and C in Moscow and the Russian Federation in 2000 - 2013. Conclusion. The retrospective analysis of the prevalence of drug addiction and viral hepatitis B and C showed the presence of common factors affecting the course of the epidemic process in the studied nosology; drug addicts still represent a risk group for infection with viral hepatitis B and C.